Evoluţii în sfera minimului de trai al populaţiei din România (calculat după metoda normativă), în perioada 1990–2005 - Mihăilescu, Adina (Calitatea Vieții, 2006)
Minimum of living standard is a reference-point which allows the measuring of the real dimension of poverty phenomena in a country or in a period of time and, of course, the measures to support people in needs to reduce poverty. Defining the concept of the living standard one refers to the consumption characteristics of population in our country. Standard method allows the knowledge, in a transparent way, of all the products which are consumed and prefered for the moment by the population and also respecting the scientifical strictness in order to have a healthy consumption important for each person from our country.